DESAIN MADRASAH SAINS INTEGRATIF: INTEGRASI SAINS DAN AGAMA DALAM PERANGKAT DAN PELAKSANAAN PEMBELAJARAN - Hasanah, Nur; Zuhaida, Anggun (EDUKASIA, 2018)
Science and religion are a unity. The difference between the two lies only in the way of view. Knowledge comes from the One God. All kinds of approaches to reality are ultimately capable of being integrated and integrated with the contemplation of the concept of God's oneness. Scientific activity is closely related to the implementation of education. The implementation of education is always based on curriculum development. The existence of curriculum development is based on the emergence of future challenges and competencies. This research aims to describe the design of integrative science and religion in the device and the implementation of learning. The research method used is descriptive qualitative, sample in this research is teacher at MTsN Kota Salatiga. The integration of science and religion is seen only in the implementation of learning, where teachers have introduced the relationship of science and religion through connecting with the verses of the Qur'an. The integration that has been implemented in the madrasah is already on the operational level.AbstrakSains dan agama merupakan satu kesatuan. Perbedaan keduanya hanya terletak pada cara pandang semata. Pengetahuan bersumber pada Tuhan Yang Maha Esa. Semua jenis pendekatan terhadap realitas pada akhirnya mampu disatupadukan dan diintegrasikan dengan melakukan perenungan tentang konsep keesaan Tuhan. Aktifitas saintifik erat hubungannya dengan pelaksanaan pendidikan. Penyelenggaraan pendidikan selalu didasarkan adanya pengembangan kurikulum. Adanya pengembangan kurikulum didasarkan pada munculnya tantangan dan kompetensi masa depan. Penelitian ini bertujuan untuk memaparkan desain madrasah sains integratif dalam perangkat dan pelaksanaan pembelajaran. Metode penelitian yang digunakan adalah deskriptif kualitatif, sampel dalam penelitian ini adalah guru di MTsN Kota Salatiga. Integrasi sains dan agama terlihat hanya pada pelaksanaan pembelajaran, di mana guru sudah mengenalkan hubungan sains dan agama melalui menghubungkan dengan ayat-ayat al-Qur’an. Integrasi yang telah diterapkan di madrasah sudah pada tatataran operasional.Kata Kunci: Integrasi, Sains, Agama, Pembelajaran